Influencia de los rincones de trabajo como estrategia metodológica en el proceso de enseñanza aprendizaje en el primer año de educación básica de la escuela fiscal mixta Eulogio Serrano Armijos. - Morocho Herrera, Rosario de Jesús (2015)
The central objective of this thesis for obtaining the title of Early Education Preschool is the determine the “influence of playful corners as a methodological strategy in the process of learning in children of first year basic education Fiscal Primary School Eulogio Serrano Armijo. The theoretical investigation, underlies the present study used several techniques, this is how the songs, drawings, movement, theater, puppetry and games besides various teaching resources and techniques to use, the same that provide clarity and guidance on the corners theories work or recreational spots. The research and theoretical basis also implies a brief historical institutional mission, vision objectives, administrative organization and human talent that counts the institution.